Neurosteroids and premenstrual dysphoric disorder - Bixo, Marie; Stiernman, Louise; Bäckström, Torbjörn (British journal of psychiatry, 2025)
Premenstrual dysphoric disorder (PMDD) is common, with at least 3% of the female population affected by one or more of the typical mood symptoms of depression, irritability, mood swings and anxiety. The cyclicity and close relationship to the luteal phase of the menstrual cycle is characteristic for this syndrome and positive allosteric modulators (PAMs) on the GABA receptor, especially allopregnanolone, are believed to be involved in the symptomatology. To summarise the research on the role of PAMs and other neuroactive steroids in the pathophysiology of PMDD. PubMed was searched for articles including the terms Premenstrual syndrome, AND neurosteroids OR allopregnanolone OR GABA OR oestradiol. Many additional publications were previously known to the authors and basic animal research was covered in a secondary step through reference lists. There is evidence that allopregnanolone, like other PAMs of the GABA receptor, is sedative in high concentrations and, in a minor proportion of the population, causes anxiety and irritability at lower levels, pointing to an inter-individual difference in sensitivity. In research comparing women with PMDD and healthy controls, differences in brain function and subcomposition of GABA receptors related to levels of allopregnanolone have been found. Also, the varying levels of neuroactive steroids in general seem to worsen the symptoms. Supressed ovulation is effective but add-back hormones are necessary to prevent severe side-effects and could cause adverse mood in these individuals. There is yet no effective treatment for PMDD available. Allopregnanolone seems to be a key provocateur of PMDD symptoms in susceptible individuals. Future research should focus on interventions that interfere with the effects of neurosteroids or the plasticity of the GABA receptor itself.